2015
DOI: 10.5424/sjar/2015133-7677
|View full text |Cite
|
Sign up to set email alerts
|

Role of the arbuscular mycorrhizal symbiosis in tolerance response against Armillaria mellea in lavender

Abstract: Lavender species form the arbuscular mycorrhizal symbiosis and are at the same time highly susceptible to white root rot. In an attempt to evaluate the response of mycorrhizal Lavandula angustifolia L. to Armillaria mellea (Vahl:Fr) P. Kumm in a greenhouse experiment, plants were previously inoculated with an isolate of the arbuscular mycorrhizal fungus Rhizophagus irregularis (former Glomus intraradices BEG 72) and the influence of the pH growing medium on the plant-symbiont-pathogen interaction was tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…What's more, soil microbes have great influence on soil biogeochemical processes including decomposition, mineralization, and retention of soil nutrients [7]. Conversely, plants also can significantly affect the composition of soil microorganisms, change soil physical and chemical properties during agricultural operations through secret phytochemicals [8]. For example, Haichar el al's researches demonstrated that plant-derived phytochemicals secreted by root are able to structure the rhizosphere microbiome by deterring or attracting certain microbial species [9].…”
Section: Introductionmentioning
confidence: 99%
“…What's more, soil microbes have great influence on soil biogeochemical processes including decomposition, mineralization, and retention of soil nutrients [7]. Conversely, plants also can significantly affect the composition of soil microorganisms, change soil physical and chemical properties during agricultural operations through secret phytochemicals [8]. For example, Haichar el al's researches demonstrated that plant-derived phytochemicals secreted by root are able to structure the rhizosphere microbiome by deterring or attracting certain microbial species [9].…”
Section: Introductionmentioning
confidence: 99%
“…The inoculum production of A. mellea was previously produced on chestnuts in an agar-malt medium [12]. To inoculate the plants with the pathogen, one chestnut colonized by A. mellea was placed in a 10 cm deep hole made in the growing substrate near the roots.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the use of microorganisms recognized as key components in the development of a sustainable agriculture, could be considered as an alternative method in the control of soil pathogens [9]. The initial increase in tolerance of white root rot caused by A. mellea through the application of arbuscular mycorrhizal fungi (AMF) has already been observed in cultivars from several plant species such as grapevine [10,11] and lavender [12]. The mechanisms involved in plant protection by AMF are not fully understood.…”
Section: Introductionmentioning
confidence: 99%